Urgent ERCP performed with single-use duodenoscope (SUD) in patients with moderate-to-severe cholangitis: Single-center prospective study - Masciangelo, Graziella; Cecinato, Paolo; Bacchilega, Igor; Masetti, Michele; Ferrari, Rodolfo; Zagari, Rocco Maurizio; Napoleon, Bertrand; Sassatelli, Romano; Fusaroli, Pietro; Lisotti, Andrea (Endoscopy International Open, 2024)
Background and study aims To assess the outcomes of urgent endoscopic retrograde cholangiopancreatography (ERCP) performed with a single-use duodenoscope (SUD) in patients with moderate-to-severe cholangitis.Patients and methods Between 2021 and 2022 consecutive patients with moderate-to-severe cholangitis were prospectively enrolled to undergo urgent ERCP with SUD. Technical success was defined as the completion of the planned procedure with SUD. Multivariate analysis was used to identify factors related to incidence of adverse events (AEs) and mortality.Results Thirty-five consecutive patients (15 female, age 81.4±6.7 years) were enrolled. Twelve (34.3%) had severe cholangitis; 26 (74.3%) had an American Society of Anesthesiologists (ASA) score ≥3. Twenty-eight patients (80.0%) had a naïve papilla. Biliary sphincterotomy and complete stone clearance were performed in 29 (82.9%) and 30 patients (85.7%), respectively; in three cases (8.6%), concomitant endoscopic ultrasound-gallbladder drainage was performed. Technical and clinical success rates were 100%. Thirty-day and 3-month mortality were 2.9% and 14.3%, respectively. One patient had mild post-ERCP pancreatitis and two had delayed bleeding. No patient or procedural variables were related to AEs. ASA score 4 and leucopenia were related to 3-month mortality; on multivariate analysis, leukopenia was the only variable independently related to 3-month mortality (odds ratio 12.8; 95% confidence interval 1.03–157.2; P=0.03).Conclusions The results of this “proof of concept” study suggest that SUD use could be considered safe and effective for urgent ERCP for acute cholangitis. This approach abolishes duodenoscope contamination from infected patients without impairing clinical outcomes.
Keywords: Stones; Cholangioscopy; Quality and logistical aspects; Hygiene